2018
DOI: 10.3892/mmr.2018.9564
|View full text |Cite
|
Sign up to set email alerts
|

Zeylenone represses the progress of human prostate cancer by downregulating the Wnt/β‑catenin pathway

Abstract: Prostate cancer (PCa) is one of the most common types of cancer in the urinary system in men. Zeylenone (Zey), a naturally occurring cyclohexene oxide, has an anticancer effect. In the present study, the role and potential mechanism of Zey in PCa were examined. The proliferative, invasive and migratory capacities of DU145 cells were analyzed using Cell Counting Kit-8, transwell and wound healing assays, respectively. The expression levels of matrix metalloproteinase (MMP)-2 and MMP-9 were determined with an EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Similarly, punicalagin, a polyphenol, exhibited apoptotic activity and inhibited the proliferation of PC3 and LNCaP cells via upregulating caspase-3/-8 expressions and decreasing vascular network formation in the CAM model, which also confirmed its antiangiogenic effect [ 166 ]. Furthermore, Zeylenone isolated from Uvaria grandiflora Roxb decreased the cell viability, invasion, and metastatic growth of human PCa (DU145) cells by downregulating the Wnt/β-catenin pathway [ 167 ]. Moreover, mangiferin has been reported to possess immunomodulatory, apoptotic, antiangiogenic, and gene regulatory effects in vitro, ex vivo, and in vivo in different cancers, especially prostate cancer [ 168 ].…”
Section: Natural Products Against Some Common Types Of Cancermentioning
confidence: 99%
“…Similarly, punicalagin, a polyphenol, exhibited apoptotic activity and inhibited the proliferation of PC3 and LNCaP cells via upregulating caspase-3/-8 expressions and decreasing vascular network formation in the CAM model, which also confirmed its antiangiogenic effect [ 166 ]. Furthermore, Zeylenone isolated from Uvaria grandiflora Roxb decreased the cell viability, invasion, and metastatic growth of human PCa (DU145) cells by downregulating the Wnt/β-catenin pathway [ 167 ]. Moreover, mangiferin has been reported to possess immunomodulatory, apoptotic, antiangiogenic, and gene regulatory effects in vitro, ex vivo, and in vivo in different cancers, especially prostate cancer [ 168 ].…”
Section: Natural Products Against Some Common Types Of Cancermentioning
confidence: 99%
“…In the present study, Zey is reported to have anti-cancer activity against prostate cancer. Zeylenone has been reported to suppress the expression of MMP-2, MMP-9 and upregulate the expression of TIMP-1 and collagen-1 in DU145 cells [173]. Curcumin is a natural compound extracted from plant Curcuma longa (Zingiberaceae).…”
Section: Mmps Inhibitors Of Natural Originmentioning
confidence: 99%
“…Zeylenone (Zey) is a natural cyclohexene oxide compound isolated from Uvaria grandiflora Roxb 6 . Since the discovery of Zey in 1997, researchers have carried out multiple studies on its manufacturing processes (synthesis/semi-synthesis), pharmacodynamics and molecular mechanism, etc, and it was considered to be an anti-tumor candidate drug with great potential [7][8][9][10] . Studies have shown that Zey could induce a large number of cell apoptosis through mitochondrial apoptosis pathway and inhibit the invasion and migration of gastric cancer cells 11 .…”
Section: Introductionmentioning
confidence: 99%
“…6 Since the discovery of Zey in 1997, researchers have carried out multiple studies on its manufacturing processes (synthesis/semi-synthesis), pharmacodynamics, molecular mechanism, etc., and it was considered to be an anti-tumor drug candidate with great potential. [7][8][9][10] Studies have shown that Zey could induce signicant cell apoptosis through a mitochondrial apoptosis pathway and inhibit the invasion and migration of gastric cancer cells. 11 Furthermore, it was reported that Zey had signicant inhibitory activity against a variety of tumor cells, which was timedependent and dose-dependent, and its anti-tumor activity was similar to that of paclitaxel.…”
Section: Introductionmentioning
confidence: 99%